MACELLA AND MAKELLOI IN ROMAN GREECE: THE ARCHAEOLOGICAL AND TEXTUAL EVIDENCE. - Evangelidis, Vasilis (Hesperia)
This article presents archaeological and textual evidence concerning buildings in Roman Greece (1st century b.c. to 3rd century a.d.) that have been identified as food markets. Such buildings often appear in inscriptions or texts under the name "makellos," which seems to be the Hellenized form of the Latin "macellum." A brief survey of the various sites where these buildings have been discovered or are known, mostly from inscriptions, is followed by a discussion that focuses on their possible usefulness as signs of Italo-Roman influence.